Effects of silver nanoparticles and ions on a co-culture model for the gastrointestinal epithelium. Issue 1 (December 2015) - Georgantzopoulou, Anastasia; Serchi, Tommaso; Cambier, Sébastien; Leclercq, Céline; Renaut, Jenny; Shao, Jia; Kruszewski, Marcin; Lentzen, Esther; Grysan, Patrick; Eswara, Santhana; Audinot, Jean-Nicolas; Contal, Servane; et al.
Abstract Background The increased incorporation of silver nanoparticles (Ag NPs) into consumer products makes the characterization of potential risk for humans and other organisms essential. The oral route is an important uptake route for NPs, therefore the study of the gastrointestinal tract in respect to NP uptake and toxicity is very timely. The aim of the present study was to evaluate the effects of Ag NPs and ions on a Caco-2/TC7:HT29-MTX intestinal co-culture model with mucus secretion, which constitutes an important protective barrier to exogenous agents in vivo and may strongly influence particle uptake. Methods The presence of the mucus layer was confirmed with staining techniques (alcian blue and toluidine blue). Mono and co-cultures of Caco-2/TC7 and HT29-MTX cells were exposed to Ag NPs (Ag 20 and 200 nm) and AgNO3 and viability (alamar blue), ROS induction (DCFH-DA assay) and IL-8 release (ELISA) were measured. The particle agglomeration in the media was evaluated with DLS and the ion release with ultrafiltration and ICP-MS. The effects of the Ag NPs and AgNO3 on cells in co-culture were studied at a proteome level with two-dimensional difference in gel electrophoresis (2D-DIGE) followed by Matrix Assisted Laser Desorption Ionization - Time Of Flight/ Time Of Flight (MALDI-TOF/TOF) mass spectrometry (MS). Intracellular localization was assessed with NanoSIMS and TEM. Results The presence of mucus layer led to protection against ROS and decrease in IL-8 release. Both Ag 20 and 200 nm NPs were taken up by the cells and Ag NPs 20 nm were mainly localized in organelles with high sulfur content. A dose- and size-dependent increase in IL-8 release was observed with a lack of cytotoxicity and oxidative stress. Sixty one differentially abundant proteins were identified involved in cytoskeleton arrangement and cell cycle, oxidative stress, apoptosis, metabolism/detoxification and stress. Conclusions The presence of mucus layer had an impact on modulating the induced toxicity of NPs. NP-specific effects were observed for uptake, pro-inflammatory response and changes at the proteome level. The low level of overlap between differentially abundant proteins observed in both Ag NPs and AgNO3 treated co-culture suggests size-dependent responses that cannot only be attributed to soluble Ag.